2001
DOI: 10.1071/wf01017
|View full text |Cite
|
Sign up to set email alerts
|

Water quality, substratum and biotic responses of five central Idaho (USA) streams during the first year following the Mortar Creek fire

Abstract: The Mortar Creek Fire burned 26 000 ha of mixed-conifer Rocky Mountain forest in July-August 1979. Changes in burn stream conditions were examined relative to reference streams for various ecological factors on two to six occasions, from October 1979 to August 1980. Factors included major ions and nutrients, suspended and benthic particulate matter, periphyton (algae), and macroinvertebrates. Elevated levels of most dissolved chemicals in the burn streams were evident soon after the fire and again during sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 29 publications
3
44
2
Order By: Relevance
“…More specialized feeders, such as shredders and scrapers, decreased in abundance. These observations are consistent with previous studies where fire effects were shown to alter functional feeding group abundances and favor community dominance by trophic generalists (Mihuc & Minshall, 1995;Minshall et al, 2001a;Vieira et al, 2004). These results also support general predictions about functional feeding groups, which suggest that shredders will respond to the loss of riparian canopy.…”
Section: Discussionsupporting
confidence: 92%
“…More specialized feeders, such as shredders and scrapers, decreased in abundance. These observations are consistent with previous studies where fire effects were shown to alter functional feeding group abundances and favor community dominance by trophic generalists (Mihuc & Minshall, 1995;Minshall et al, 2001a;Vieira et al, 2004). These results also support general predictions about functional feeding groups, which suggest that shredders will respond to the loss of riparian canopy.…”
Section: Discussionsupporting
confidence: 92%
“…Although the post-fire increase in NO 3 À , TKN, and total P was not seen in the unburned streams, the measured post-fire concentration was within the pre-fire range of concentrations (Table 7; Bêche, 2005). In general, the direct effects of most fires (prescribed or wildfire) on streams (ash deposition and fire-induced temperature increases) are usually negligible (e.g., Minshall et al, 2001a;Minshall, 2003). However, in the case of some severe wildfires, ash deposition and diffusion of smoke into the water can dramatically increase phosphorous and nitrogen (e.g., Spencer and Hauer, 1991;Minshall et al, 1997).…”
Section: Water Chemistrymentioning
confidence: 97%
“…Current management practices avoid the use of prescribed burning near aquatic ecosystems (e.g., Erman, 1996) with few exceptions (e.g., Chan, 1998;Huntzinger, 2003). These practices are designed to prevent the potentially negative impacts (e.g., increased erosion or altered hydrographs) that have been found to occur after wildfires (e.g., Roby and Azuma, 1995;Rinne, 1996;Minshall et al, 1995Minshall et al, , 1997Minshall et al, , 2001a.…”
Section: Introductionmentioning
confidence: 97%
“…Seasonal variability can be due to geochemical weathering, as observed in western Montana (Nagorski et al, 2003), or snowmelt runoff (Sickman et al, 2003;Stottlemyer and Troendle, 1992). Primary producers remove N and P (Minshall et al, 2001;Mulholland et al, 2000), and there can be a high demand for N species, especially during the summer (Peterson et al, 2001). However, compared with other land uses, forestland streams generally have relatively low N and P concentrations (Omernik, 1977;Clark et al, 2001;Ice and Binkley, 2003).…”
Section: Introductionmentioning
confidence: 95%